Epidemiological Situation of African Swine Fever in Lake Alaotra Region (Madagascar) and Possible Consequences on the Organization of Disease Control and Surveillance - T. Randriamparany; A. Grenier; I. Tourette; C. Y. Maharavo Rahantamalala; D. Rousset; R. Lancelot (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux, 2005)
An epidemiological survey was undertaken from April to July 2004 at the slaughterhouse of Ambatondrazaka, in the region of lake Alaotra (Madagascar), to study the incidence of the African swine fever (ASF). Out of 200 pig carcasses examined, 155 (78%) presented ASF-like lesions: hemorrhagic lymph nodes and/or discolored kidneys with petechiae on their surfaces. Samples were taken and tested for the ASF virus using an antigen-ELISA technique and a PCR method. Eighteen percent of suspect carcasses were infected: prevalence of 14% (95% confidence interval: 9 to 19%). The PCR test was twice more sensitive than the ELISA test, and twice cheaper. In places where both equipments and technicians are available, PCR should be the preferred technique for this kind of survey. Farms were difficult to trace back from the carcasses: it was possible in 32 cases (16%). The only risk factor identified was the previous occurrence of swine fever in the farms, as reported by the breeders. To improve the control and surveillance of ASF in Ambatondrazaka, the most urgent measures would be to build a new slaughterhouse away from the town and market, to ban pigs straying and to set up a traceability system between slaughterhouse and farms. The relative importance of African and classical swine fevers should also be specified to improve control and epidemiosurveillance.